Determinants of Satisfaction of Learning among Nursing Students of Nepal - Sah, Durga Kumari; Das, Dorwin (Journal of Advanced Academic Research, 2024)
Background: Learner satisfaction and its importance is acknowledged globally in nursing education. The institutions are striving to develop settings that prioritize not only comprehensive and relevant curricula but also student satisfaction and well-being. Objectives: To assess determinants of satisfaction of learning among nursing students in Nepal. Methods: A descriptive cross-sectional study was conducted among 293 nursing students from Purbanchal University in Bagmati Province, Nepal. The data was gathered utilizing a Student Survey Outcome tool. The data was analyzed using descriptive statistics and the chi-square test was utilized to determine the association between the level of satisfaction with learning and socio-demographic factors. Results: The findings of the study revealed that 1.4% of the participants were not satisfied with the learning, 5.8% were satisfied and 92.8% were highly satisfied with learning. The level of learning satisfaction was significantly associated with the educational status of the father, the occupation of the mother, and the nursing background (p<0.05). Conclusion: The study concludes that nursing students have a high level of learning satisfaction. Nursing colleges can focus on student-centred learning approaches to further enhance the learning satisfaction of students.